Strengthening Legal Protection for Medical Personnel in Indonesia’s Conflict-Affected Areas - Ontran Sumantri Riyanto; Mei Rianita Elfrida Sinaga; Dian Ratu Ayu Uswatun Khasanah (Immortalis Journal of Interdisciplinary Studies, 2026)
Medical personnel serving in conflict-affected areas face risks of violence, security threats, and disruptions to healthcare delivery that may endanger their safety while simultaneously undermining the continued realization of the population’s right to health. Indonesia has established a legal basis for protection through national health law and International Humanitarian Law; however, a gap remains between normative guarantees and protection that can be effectively implemented in practice. This study aims to construct an integrated legal protection model for medical personnel in conflict-affected areas of Indonesia. It employs a qualitative approach with a socio-legal research design based on document analysis and online sources. Data were obtained from legislation and regulations, institutional documents, scholarly literature, reports issued by national and international organizations, and credible online news sources, and were subsequently analyzed using qualitative thematic content analysis and source triangulation. The findings indicate that the principal challenge in protecting medical personnel lies not merely in the absence of legal norms, but in the lack of integration among protection mechanisms before, during, and after deployment. This study develops a continuum of legal protection that connects risk assessment, security measures, deployment protocols, reporting and early-warning systems, legal assistance, victim recovery, investigation, and accountability across four dimensions: preventive, operational, remedial, and accountability protection. The model shifts the orientation of protection from a reactive and fragmented approach toward a preventive, continuous, and human-centered system. Strengthening its implementation requires operational regulations and inter-agency coordination to safeguard medical personnel while ensuring the continuity of healthcare services in conflict-affected areas.